English for specific technical and engineering academic purposes: an analysis on ESL practitioners’ challenges - Nor Yazi, Khamis; Azwin Arif, Abdul Rahim; Supyan, Hussin; Suriya Kumar, Sinnadurai (2018)
The facilitation of English for Specific Engineering Academic Purposes approach at Malaysian technical and engineering tertiary institutions is an effort to revitalise the pedagogical methods of ESL learning and communication skills at the institutions. A close examination on the ESL practitioners’ context has indicated a critical gap between the diversified requirements of skills and sound pedagogical models to determine the practitioners’ quality. In understanding the necessity of the approach, this study aims to investigate and explore the challenges faced by the practitioners facilitating the approach. The study comprised data gathered from an online survey on the 42 ESL practitioners and semi structured interviews of the 14 ESL experts in technical and engineering fields. A self-assessed instrument with a five-Likert scale of importance was used to gauge the practitioners’ knowledge of the approach. Interview questions for the experts were later developed to find out reasons about the earlier findings. Frequencies and percentages, and Braun and Clarke’s (2006) six-stage method of thematic analysis (TA) were used to analyse the data. Findings from the both inquiries on the practitioners and experts respectively revealed several challenges; therefore, the necessity of wider knowledge and understanding of the approach in facilitating the context became the prevalent competency for the practitioners in overcoming the challenges. The practitioners’ competency was substantially indispensable because it could affect their learners’ interest in learning the skills as well as in understanding the content subject. The challenges faced by the practitioners call for a specific professional development training, which was hardly available, to elevate their status and recognition. Subsequently, it implicates the need for the institutions and local quality agencies to review and specify the requirement and guideline for ESL practitioners teaching the skills in a specific academic technical and engineering context.